1973
DOI: 10.1128/aem.26.4.636-637.1973
|View full text |Cite
|
Sign up to set email alerts
|

Potential Production of Sterigmatocystin on Country-Cured Ham

Abstract: In laboratory media, 10 of 16 isolates of Aspergillus versicolor from countrycured ham were capable of producing sterigmatocystin. Three of these isolates were tested and found to produce sterigmatocystin on country-cured ham after 14 days of incubation at 20 or 28 C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Included among these aspergilli are members of the Aspergillus glaucus and A. restrictus groups, A. candidus, A. ochraceus, and A. versicolor. Of particular interest is A. versicolor because of its frequent occurrence in stored grains and food commodites (3,5,6,9,10,15,22,23) and its ability to elaborate the carcinogen sterigmatocystin (12,16). Some members of the A. flavus, A. nidulans, A. ustus, and A. glaucus groups, as well as Chaetomium species (21) and the field fungus Bipolaris (12), are also known to produce sterigmatocystin (13,16).…”
mentioning
confidence: 99%
“…Included among these aspergilli are members of the Aspergillus glaucus and A. restrictus groups, A. candidus, A. ochraceus, and A. versicolor. Of particular interest is A. versicolor because of its frequent occurrence in stored grains and food commodites (3,5,6,9,10,15,22,23) and its ability to elaborate the carcinogen sterigmatocystin (12,16). Some members of the A. flavus, A. nidulans, A. ustus, and A. glaucus groups, as well as Chaetomium species (21) and the field fungus Bipolaris (12), are also known to produce sterigmatocystin (13,16).…”
mentioning
confidence: 99%
“…Abundant mold growth is often observed on the surface of country-cured hams and is associated with sufficient age time (2). However, some researchers have reported that fungi isolated from country-cured hams are capable of producing mycotoxins (3,5,9,11). In addition, many people find the appearance of mold on food distasteful.…”
mentioning
confidence: 99%
“…They also found that water or ether extracts of all mouldy corn samples exhibited some degree of toxicity. More than 800 mould cultures were isolated and identified from country cured hams and fermented sausages (Leistner & Ayres 1968;Sutic et al 1972). Aflatoxin-, ochratoxin-, sterigmatocystin-and citrinin-producing strains were isolated and identified from country cured hams (Escher et al 1973;Halls & Ayres 1973;Strzelecki et al 1969;Sutic et al 1972;Wu et al (1974~).…”
mentioning
confidence: 99%
“…More than 800 mould cultures were isolated and identified from country cured hams and fermented sausages (Leistner & Ayres 1968;Sutic et al 1972). Aflatoxin-, ochratoxin-, sterigmatocystin-and citrinin-producing strains were isolated and identified from country cured hams (Escher et al 1973;Halls & Ayres 1973;Strzelecki et al 1969;Sutic et al 1972;Wu et al (1974~). Wu et al (1974b)later found that many of the 89 cultures of Aspergillus and 54 cultures of Penicillium isolated from aged, cured meats were toxic to chick embryos.…”
mentioning
confidence: 99%